Improving the quality of sexual life in postmenopausal women: a qualitative study - Elnaz Haji Rafiei; Hedyeh Riazi; Jamal Shams; Hamid Alavi Majd (BMC Public Health)
Abstract Background Postmenopausal women frequently encounter a range of physical, emotional, and relational challenges. One aspect that is frequently overlooked is the impact of menopause on sexual life. The objective of this study was to elucidate solutions to enhance the quality of sexual life of postmenopausal women. Methods This qualitative conventional content analysis study was conducted from December 2022 to August 2023 in Qazvin, Iran. Using purposive sampling with maximum variation, data were collected through in-depth interviews with 21 participants, comprising 15 postmenopausal women and 6 experts, for a period of 3 months. Results From the interviews, a total of 495 initial codes were identified and subsequently organized into 39 subcategories and 11 categories. This rigorous coding process led to the extraction of three themes: “Understanding and managing influencing factors”, “Raising awareness and a new perspective on sexual relationships”, and “Accepting and managing postmenopausal changes”. Conclusion By identifying the key themes that emerged from this study, we can gain a deeper understanding of the promotion of healthy and positive sexual relationships, as well as the development of strategies for addressing the challenges and complexities that arise in these relationships. The findings can serve as a basis for the implementation of interventions and the planning of initiatives aimed at the promotion of the quality of sexual life of postmenopausal women.